Collaborative Governance Pada Pemanfaatan Infrastruktur Kepemudaan dan Olahraga Kota Bandung (di Kecamatan Antapani Tahun 2023) - Naomi Glori Natalia; Muradi Muradi; Dede Sri Kartini (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Bandung city has great potential in the field of youth and sports, which is marked by the first national level youth title given by the Indonesian Ministry of Youth and Sports as well as various achievements in national and international sports. To improve the quality of this sector, more attention from the government is needed, one of which is in terms of infrastructure. One of the sub-districts of Bandung City which has quite a large youth and sports infrastructure is Gasibu Mini, Antapani Sub-district. This research was motivated by collaboration carried out by the Antapani District government with various stakholders in utilizing the Gasibu Mini sports infrastructure and Antapani Youth Space. Researchers use collaborative governance assessment theory which consists of three dimensions. The method used is descriptive with a qualitative approach. The result is that in the stakeholders representation dimension, the Antapani District has made decisions that adequately represent the interests of stakeholders and regularly communicates. In the distribution of authority dimension, there is a formal and informal division of authority, but supervision carried out by the District is not optimal and there is no MoU for implementing collaboration. Dimensions of accountability mechanisms, accountability is carried out by actors but there are still limited resources. The conclusion shows that the implementation of collaborative governance in the use of youth and sports infrastructure in Antapani District has been implemented but is not optimal in several dimensions.